Understanding the Mental Health of Students and Professors within Universities: a Cross-sectional, Multicultural Analysis across Three European Countries - García Salido, Cristina; Ramírez Baraldes, Estella; Miedaner, Felix; Hasseler, Martina; Hlubučková, Andrea; Garcia Gutierrez, Daniel (Investigación y Educación en Enfermería, 2025)
Objective. To analyze the relationship among the professional role (student or professor), geographic location, and mental health in the university community after the COVID-19 pandemic. Methods. Quantitative cross-sectional study conducted at universities in Spain, Germany, and the Czech Republic. Non-probability convenience sampling was used, obtaining a sample of 449 participants (372 students and 77 professors). Mental health was assessed using the Scale for Mood Evaluation (EVEA), measuring sadness-depression, anxiety, anger-hostility, and happiness. Results. Significant differences were found between students and professors, with students reporting higher levels of sadness-depression (3.8 vs. 2.4; p<0.001), anxiety (4.6 vs. 2.9; p<0.001), and anger-hostility (3.4 vs. 2.5; p<0.01). Professors showed higher levels of happiness (6.7 vs. 5.4; p<0.001). In addition, differences among countries were observed: participants from Spain showed higher levels of sadness-depression and anxiety compared to Germany and the Czech Republic. Conclusion. University students have greater emotional vulnerability than professors, highlighting the need for differentiated psychosocial support strategies in the academic setting.